Computer Supported Qualitative Research New Trends on Qualitative Research - Costa, António Pedro; Reis, Luís Paulo; Moreira, António (Advances in Intelligent Systems and Computing, 2019)
This book includes a selection of papers presented at the Third World Conference on Qualitative Research (WCQR2018), held in Lisbon, Portugal on October 17-19, 2018. The WCQR2018 focused on four main fields of application (Education, Health, Social Sciences, and Engineering and Technology) and seven main subjects: Rationale and Paradigms of Qualitative Research; Systematization of Approaches with Qualitative Studies; Qualitative and Mixed Methods Research; Data Analysis Types; Innovative Processes of Qualitative Data Analysis; Qualitative Research in Web Contexts; and Qualitative Analysis with the Support of Specific Software. Given its breadth of coverage, the book offers a valuable resource for academics, researchers, teachers and students seeking information on the above topics, and on the use of Computer Assisted Qualitative Data Analysis (CAQDAS). .